Imidazolium Ionic Liquids, Imidazolylidene Heterocyclic Carbenes, and Zeolitic Imidazolate Frameworks for CO2 Capture and Photochemical Reduction - Wang, Sibo; Wang, Xinchen (Angewandte Chemie International Edition, 2016)
Imidazolium ionic liquids (ILs), imidazolylidene N‐heterocyclic carbenes (NHCs), and zeolitic imidazolate frameworks (ZIFs) are imidazolate motifs which have been extensively investigated for CO2 adsorption and conversion applications. Summarized in this minireview is the recent progress in the capture, activation, and photochemical reduction of CO2 with these three imidazolate building blocks, from homogeneous molecular entities (ILs and NHCs) to heterogeneous crystalline scaffolds (ZIFs). The developments and existing shortcomings of the imidazolate motifs for their use in CO2 utilizations is assessed, with more of focus on CO2 photoredox catalysis. The opportunities and challenges of imidazolate scaffolds for future advancement of CO2 photochemical conversion for artificial photosynthesis are discussed. Around the block: Imidazolate building blocks can be utilized in three different ways for the adsorption, activation, and photoreduction of CO2: as components of ionic liquids, N‐heterocyclic carbenes, or zeolitic imidazolate frameworks (see picture). The recent developments and existing shortcomings of imidazolate motifs for CO2 utilization, with focus on CO2 photoreduction catalysis, are summarized.